Comparison of pharmacist knowledge, perceptions and training opportunities regarding maternal-fetal medicine in Canada, Qatar and Uganda. (November 2014) - Bains, Serena; Kitutu, Freddy E.; Rahhal, Ala'a; Abu Samaha, Rana; Wilby, Kyle J.; Rowe, Hilary
Background: Although pharmacists have great potential to modify and optimize drug therapy in pregnancy and lactation, current literature demonstrates that they do not routinely provide this care and often feel ill equipped to do so. The objective of this study was to determine pharmacists' knowledge and perceptions of maternal-fetal medicine in Canada, Uganda and Qatar. Secondary objectives were to determine factors associated with pharmacists' knowledge and to characterize training opportunities and resources available to practising pharmacists. Methods: A cross-sectional survey using online software (SurveyMonkey) was sent to the e-mails of potential research participants. Practising pharmacists and resident pharmacists in British Columbia, Canada; the country of Qatar; and the country of Uganda were eligible for inclusion. The survey was designed to assess knowledge and perceptions, and to create a baseline inventory of current practice and information resources used in practice. Results: The mean knowledge assessment scores of pharmacists in Canada, Qatar and Uganda were 62.9%, 53.3%, and 57.7%, respectively ( p < 0.05). Pharmacists in British Columbia scored higher on knowledge assessment than pharmacists in Qatar ( p < 0.05), but other country comparisons were not significant. No predefined factors (gender, years of experience, practice area or parental status) were found to be significant in determining the knowledge score. More than two-thirds of pharmacists expressed interest in participating in continuing education opportunities in maternal-fetal medicine. Conclusion: Pharmacists have differing levels of knowledge in the area of maternal-fetal medicine. Continuing education and degree curricula should be reviewed and developed to fill the knowledge gaps of student pharmacists and practising pharmacists in maternal-fetal medicine.